The contribution of Land Use Consolidation policy to food and nutrition security of women farmers : a case study of the farmers involved in potato farming, food availability in Nyabihu district, Rwanda - Mutangiza, Odette (SLU/Dept. of Urban and Rural Development, 2019)
The overgrowing population in Rwanda and the persistent fragmentation of households’ plots induced the land use designs to be restructured. The Government of Rwanda introduced the Land Use Consolidation (LUC) policy to manage land fragmentation, and shift from subsistence to a market oriented agriculture. This thesis explores the contribution of LUC policy to food and nutrition security of women farmers, a case study of the farmers involved in potato farming in Nyabihu district, Rwanda. The empirical data was collected through a variety of qualitative research methods during field work in Nyabihu district. These data were analyzed through the agriculture – nutrition conceptual framework. Stories on how women farmers in the district perceived the LUC policy Vis a Vis their food security are the central pillars of the thesis discussion. However, the focus of analysis is on the food production and women’s empowerment pathways. Further, the concept of institution helped to explore the roles played by different institutions in the adoption of LUC policy in this thesis. The findings of this thesis revealed that access to inputs, trainings, and a stable market are the most important institutions in the adoption of LUC policy in Nyabihu district. The findings also revealed that LUC improved the availability of food in this region through the increase in potato productivity. However, the food and nutrition security at the household level was not achieved due to the high cost of potato production. LUC had positive impacts on well off women farmers in this district than the poor ones; its implementation plan was a bottom up approach and women farmers participated in all decision making. LUC also helped many women farmers to shift from subsistence to business farming. Therefore, they were able to have access on money and participate in other off-farm activities.